2016
DOI: 10.3791/54437
|View full text |Cite
|
Sign up to set email alerts
|

Deferred Growth Inhibition Assay to Quantify the Effect of Bacteria-derived Antimicrobials on Competition

Abstract: Competitive exclusion can occur in microbial communities when, for example, an inhibitor-producing strain outcompetes its competitor for an essential nutrient or produces antimicrobial compounds that its competitor is not resistant to. Here we describe a deferred growth inhibition assay, a method for assessing the ability of one bacterium to inhibit the growth of another through the production of antimicrobial compounds or through competition for nutrients. This technique has been used to investigate the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…Negative as well as positive bacterial interactions based on competition/cooperation can be monitored with growth inhibition assays as described by Moran et al . (Moran et al, 2016). The assay is used to detect growth inhibition and its degree or growth promotion of the neighboring bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative as well as positive bacterial interactions based on competition/cooperation can be monitored with growth inhibition assays as described by Moran et al . (Moran et al, 2016). The assay is used to detect growth inhibition and its degree or growth promotion of the neighboring bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…First, all 231 isolated bacterial strains were grown on MB agar plates at 30 °C overnight (Moran, Crank, Ghabban, & Horsburgh, 2016). Out of those 231 strains, 203 formed compact bacterial lawns on the agar plates under the selected growth conditions and were subsequently used for the growth inhibition assay as follows.…”
Section: Methodsmentioning
confidence: 99%
“…The antagonistic activity of all C. accolens clinical strains and a culture collection strain, C. accolens ATCC 49726 was evaluated against S. aureus clinical isolates and S. aureus ATCC 25923 (from ATCC, Manassas, VA, USA) using deferred growth inhibition assays as described previously [ 34 ] with modifications. Briefly, a 48 h C. accolens culture (20 µL, approximately 10 8 cells) in TSB (test inhibitor strains) was pipetted onto the centre of a TSA plate supplemented with 0.8% Tween 80 and incubated for 48 h at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…It confirmed that the impact of ABP on the populations of L. monocytogenes varied according to the conditions of its environment. The reason for visible inhibition at 1/10th and 1/100th strength of TSA may be attributed to competitive exclusion, i.e., increased competition for the available nutrients in the medium (Moran et al, 2016). In a study conducted by Buchanan and Bagi (1999), it was observed that P. fluorescens was able to inhibit L. monocytogenes, and this inhibition was dependent on temperature, pH and sodium chloride levels in brain-heart infusion broth.…”
Section: Discussionmentioning
confidence: 99%